Al-Hiwār baina al-Imān 'inda Nurcholish Madjid - Ari Budi Santoso (Departement of Comparative Study of Religions, 2022)
Interreligious dialogue has been a significant topic in recent years, especially in the effort to create harmony between religious communities. Nurcholis Madjid, a prominent Indonesian Muslim scholar, has advocated for the concept of pluralism in his efforts to promote interfaith dialogue. However, some of his thoughts have been controversial among religious people. Using descriptive and analytical methods, as well as a theological approach, this article aimed to reveal and criticize Nurcholish Madjid's inclusive-pluralist theology. In conclusion, Nurcholish Madjid believes that all religions, including Islam, Judaism, Christianity, and Shabiin, are true as long as they believe in Allah, believe in the Day of Judgment, and do good. He argues that Islam is a universal religion and pluralism is sunnatullah, which means it has been occurring since the beginning of time. While Nurcholish Madjid's approach to interreligious dialogue may seem inclusive and tolerant, it deviates from the core teachings of Islam. According to the Qur'an, Islam is the only true religion, and it cannot be equated with any other faith. Pluralist inclusive theology is not a way to achieve inter-religious harmony but instead creates new problems because it reduces the meaning and identity of religions. As such, a critical evaluation of his thoughts is necessary to understand the implications of pluralism in the context of Islam.